2006
DOI: 10.1016/j.juro.2006.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Are Small Renal Tumors Harmless? Analysis of Histopathological Features According to Tumors 4 Cm or Less in Diameter

Abstract: The aggressive potential of small renal cell carcinoma increases dramatically beyond a tumor diameter of 3 cm. Given the difficulty in measuring tumor diameters reliably with sequential imaging studies, the threshold for selecting patients for a surveillance strategy should be set well under this parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
157
4
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(185 citation statements)
references
References 16 publications
13
157
4
7
Order By: Relevance
“…On the other hand, only 6.3-7.1% are benign for lesions larger than 7.0 cm in diameter [21]. It has been reported that renal masses 3 cm in diameter have a more aggressive potential, resulting in more incidences of metastases [22,23] (Tables 2 and 3). Moreover, the proliferation rate should also be considered.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, only 6.3-7.1% are benign for lesions larger than 7.0 cm in diameter [21]. It has been reported that renal masses 3 cm in diameter have a more aggressive potential, resulting in more incidences of metastases [22,23] (Tables 2 and 3). Moreover, the proliferation rate should also be considered.…”
Section: Discussionmentioning
confidence: 98%
“…RN, KBY gelişimi için önemli bir risk faktörüdür. Küçük renalkortikal tümörlerin yaklaşık %20'sinin benign patolojiye sahip olduğu için, RN'nin artık altın standart yöntem olarak görülmemesi gerektiği kabul edilmiş bir gerçektir (6,18). Mayo klinik ekibinin 2000 yılında tek taraflı RHK, diğer böbreği ve kreatinin değeri normal olan hastalarda RN ile NKC'yi karşılaştırdığı bir çalışmada kreatinin değerinin >2 mg/dl olması şeklinde tanımlandığı kronik renal yetmezlik, 10 yıllık takip sonunda RN grubunda %22,4 iken NKC grubunda %11,6 olarak bulunmuştur.…”
Section: Discussionunclassified
“…Numerous studies have reported a higher proportion of benign pathology for small renal masses treated surgically. 6,9,11,12,[16][17][18][19] In a series by Schachter and colleagues, 26.3% of masses ≤4 cm were benign. 12 Similarly, Pahernik and colleagues reported a proportion of benign disease of 24.4% in a series of 504 patients treated with partial nephrectomy over 25 years.…”
Section: Discussionmentioning
confidence: 99%